Potensi Tindak Pidana Korupsi di Lingkungan Akademisi - Argo Pambudi (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
This paper intends to describe bureaucratic interventions in academic activities that have contents the potential that lead to create corruption in the university environment. If there is no serious treatment from the authorities to prevent it, then it is not impossible that the situation will explode into a real corruption. It's just a matter of time, when officials process it legally. This situation will clearly disrupt the productivity and reputation of academics staf in higher education in the future.